CLINICAL, NEUROLOGICAL AND IMMUNOLOGICAL PARAMETERS IN CHILDREN WITH HYMENOLEPIDOSIS AND PROTOZOAN INVASIONS - Khamidova Nargiza Kosimovna (Galaxy International Interdisciplinary Research Journal, 2023)
The analysis of clinical and immunological parameters in children with hymenolepidoses and neurological complications revealed an increase in antigen-binding lymphocytes and brain tissue antigens in patients with combined invasion of intestinal tissue antigens in the group of children with isolated hymenolepidoses.